Minimum wage Policy and Economic Development in the long run: The Case Study of Thailand - patchimnan, attakrit (King Prajadhipok’s Institute Journal, 2020)
The efficiency of minimum wage policy management is very important for economic development and political stability because the minimum wage rate reflects the effective management of labor policies, and because the labor policy is related to correlated with the rate of employment, which and employment index that reflects the lower level of inequality of income distribution. However, the minimum wage policy as monopolistic characteristics on political interests and decisions of the government indicate that minimum wage can be a form of populism, for example, by making minimum wage policy cater to the satisfaction of various interest groups. Therefore, a minimum wage of 300 baht per day would result in increasing unemployment when Thailand puts ASEAN economic community integration into effect. Moreover, effective minimum wage policy must take into account the level of productivity, employment rate, and the level of economic inequality, all of which would be affected by the influx of laborers from outside markets into the labor force.